Puzzle sebagai Solusi Peningkatan Motivasi Belajar Siswa - Suratiningsih Suratiningsih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The research aims to describe the puzzling media as a solution to increase the learning motivation of elementary /MI student. This research is library research. It is a method that the data which is needed in completing research comes from library sources i.e. include books, encyclopedias, dictionaries, journals, documents, magazines, etc as well as various sources on the internet. The data collection technique used in this research is documentation. Documentation means looking for data about things in the form of notes, books, papers, articles, journal, and so on. Then, the data analysis technique used in this study is content analysis. In this analysis, the process of selecting, comparing, and combining various meanings will be found to be relevant. The media is an intermediary or introduction. Puzzle media can improve the students’ motivation to keep trying to solve problems. It is fun for students because it can be repeated. The challenges in the puzzle game will give you an addictive effect to always try and try until they are successful.